Open Versus Closed Kinetic Chain Exercise: a Comparison of Walking Capacity in Chronic Post-Stroke Phase - Kukuh Wibisono; Rahmi Isma (Indonesian Journal of Physical Medicine & Rehabilitation, 2022)
Introduction: The chronic post-stroke phase is often accompanied by various sensory, cognitive, motoric, coordination, and balance impairments. Decreased strength and motoric control contribute to walking capacity in patients with stroke. This study aims to evaluate the effect of Open Kinetic Chain (OKC) vs Closed Kinetic Chain (CKC) exercise on walking capacity in the chronic post-stroke phase. Open Kinetic Chain (OKC) and Closed Kinetic Chain (CKC) were reported to improve functional mobility and balance in the chronic post-stroke phase. However, there is a lack of studies emphasizing the effect of OKC and CKC on walking capacity. Methods: This study is a quasi-experimental pre- and post-controlled trial group design. Twenty subjects were randomized into two groups of equal size: the CKC group (n=10) and the OKC group (n=10). There was one subject from each group who dropped out at the end of the study. CKC and OKC groups were trained for 6 weeks. The walking capacity was measured with 2 Minutes Walking Test (2WMT). Results: 2WMT results showed improvement in both groups after 6 weeks of intervention, 56,17 ± 10,95 ± to 57,43 ± 11,29 in CKC group (p<0.001) and 57,04 ± 8,58 to 58,19 ± 8,77 in OKC group (p<0.002). Conclusion: CKC and OKC exercise significantly improve the 2WMT results after 6 weeks of intervention. Keywords: Chronic post-stroke phase, walking capacity, open kinetic chain exercise, closed kinetic chain exercise